LncRNA-ECM is overexpressed in esophageal squamous cell carcinoma and promotes tumor metastasis - Yao, Juan (Oncol Lett, 2018)
The aim of the present study was to investigate the expression of long non-coding(lnc) RNA-extracellular matrix (ECM) in esophageal squamous cell carcinoma (ESCC) and its effect on ESCC metastasis. Using reverse transcription-quantitative polymerase chain reaction (RT-qPCR), the expression of lncRNA-ECM in ESCC tissues was investigated and compared with that in corresponding adjacent tissues. In addition, the expression of lncRNA-ECM in the human ESCC cell lines TE-1, EC9706, KYSE150, Eca109 and KYSE30 was also detected and compared with that in the normal esophageal mucosal epithelial cell line HET-1A. The clinicopathological association between lncRNA-ECM and ESCC was assessed. Silencing and overexpression of lncRNA-ECM in ESCC TE-1 and Eca109 cells determined the correlation between lncRNA-ECM expression and ESCC invasion and metastasis. The possible target genes of lncRNA-ECM were predicted and verified by bioinformatics analysis and experimental results. The expression level of intercellular adhesion molecule 1 (ICAM1) was detected in ESCC tissues by RT-qPCR and the correlation between the expression of ICAM1 and lncRNA-ECM was analyzed. Changes in the expression of ICAM1 in ESCC TE-1 and Eca109 cell lines were evaluated after knocking down lncRNA-ECM and transfection of lncRNA-ECM overexpression plasmids. The expression level of lncRNA-ECM in the tissues of ESCC with lymph node metastasis were significantly increased compared with ESCC with no lymph metastasis (P<0.05). LncRNA-ECM silencing notably reduced the invasion and metastasis of TE-1 and Eca109 cells, while lncRNA-ECM overexpression promoted the invasion and metastasis of the two cell lines. The expression level of ICAMI was directly correlated with the expression of lncRNA-ECM, suggesting that ICAM1 may be the downstream target gene of lncRNA-ECM. LncRNA-ECM was revealed as being overexpressed in ESCC. LncRNA-ECM expression was positively correlated with metastasis and may affect the metastasis of ESCC through ICAMI regulation. These findings indicate that lncRNA-ECM may be promising as a novel biomarker for the diagnosis and prediction of prognosis for ESCC, and it may also serve as a novel therapeutic target for ESCC.